Analisis Perkembangan Obligasi Syariah (Sukuk) Serta Pengaruh Sukuk Terhadap Pasar Modal Syariah - Faizah Hasibuan; Faza Halillah; Khairina Tambunan (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This research was made to analyze the developments that occur in Islamic bonds or known as sukuk and see whether this sukuk has a significant impact on Islamic capital, especially in Indonesia. In this study, researchers used descriptive qualitative methods. In this study, documentation studies were carried out in collecting data through observation and documentation. This research shows that sukuk has increased significantly, as of January 2022 based on the Sharia Bond Statistics Data of the Financial Services Authority has touched the figure of Rp. 35.02 Trillion. Meanwhile, the growth of sukuk every year has a significant impact on the development of the Islamic capital market. so that the existence of this sukuk has a positive impact on the capital market in Indonesia.